Satanic sexuality: understanding Satanism as a diversity issue for sex and relationship therapists. Issue 3 (3rd July 2022) - Sprankle, Eric; Danielson, Samuel; Lyng, Tayler; Severud, Mariah
Abstract: Appropriating the mythology of Satan as a god of carnality, modern Satanism began as a new religious movement in 1966 with the founding of the Church of Satan. Since then, the religion has experienced numerous schisms and factions, most recently with the formation of The Satanic Temple in 2012. Despite differences in the role of esoteric elements in the religion and other theological or governance reasons for division, Satanists are united in their shared values of sexual liberation and viewing sexuality as a form of authentic self-expression important to their religious beliefs. Conceptualizing Satanism as a non-dominant, sex-positive religion, sex and relationship therapists should understand how Satanists' sexuality can benefit from a religious belief in sexual liberation, but can also be hindered by religious minority stress. The historical development of modern Satanism, the intersections of Satanism and gender, sexual orientation, and relationships, and guidelines for therapists working with Satanist clients are discussed. LAY ABSTRACT: Modern Satanism is an oft-misunderstood new religious movement. This paper provides an overview of the development of Satanism with special attention to its beliefs and practices relevant to sexuality. Guidelines are presented for sex and relationship therapists on how to appropriately assess and treat Satanist clients.